Early Health, Risk Aversion and Stock Market Participation - Petri Böckerman; Andrew Conlin; Rauli Svento (Institute of Labor Economics (IZA), 2019)
To examine the relationship between early health status and financial decisions in adulthood, we link information on birth weight in 1966 from the Northern Finland Birth Cohort to data from the Finnish Central Securities Depository over the period of 1995-2010. We find that persons predisposed to poor health status in early childhood (indicated by low birth weight) avoid participating in the stock market in adulthood. The link between birth weight and stock market participation is partially explained by the fact that poor early health status leads to risk aversion. Early health status is not significantly related to the portfolio's value-growth tilt.
Keywords: I10; G11; 330; health status; birth weight; stock market participation